The Behaviour of Health Faculty Students Responding to Hoaxes Related Covid-19 on Social Media - Haikal Haikal; Ratih Pramitasari; Alvin Maulana Firza Yanuar; Nis Syifa’ur Rahma (Universitas Ahmad Dahlan, 2021)
Background: Hoax is still a problem in the era of information disclosure and technological advances currently. News or information containing hoax related to Covid-19 affects the handling effort of the Covid-19 pandemic. This research aimed to describe the behavior of health faculty students in responding to the hoaxes associated with Covid-19 on social media. Method: This research was a descriptive study. The sampling technique used was random sampling. The samples were 384 students who were required to complete the questionnaire. The statistical test used was descriptive statistical analysis. Results: The results obtained in this study were that respondents considered Facebook as the most widely used social media for spreading hoaxes (68%). Respondents thought that cross-checking the accuracy and validity of information is a step that should be performed when receiving hoax news (85%). Respondents stated that they dug up information through official government websites regarding the handling of Covid-19 to check the statement's truth (65%). Some respondents did not cross-check the news or information related to Covid-19 due to the assumption that someone else had done it. Conclusion: Most respondents have cross-checked news or information about Covid-19. Extracting information through official government websites on handling Covid-19 has also been taken to check the accuracy and validity of the statement.